Analysis of Generalized Self-Excited Vibrations - Wernerowski, K. (Engineering Transactions, 1994)
The asymptotic nonlinear method is applied to salve the generalized equation of the self-excited vibration. In the last several decades, increased interest in the study of asymptotic analysis is observed, based mainly on application of the exact convergence. The solution describes better the self-excited vibrations of a real mechanical system.